Owen Jones, Gottfried Semper and the anthropological origins of ornamental art (Palíndromo, 2020)
Following the first London Universal Exhibition in 1851, architects Owen Jones and Gottfried Semper appealed to primitive cultures to affirm the anthropological nature of ornamental art.
Keywords: Owen Jones; Gottfried Semper; primitive art; ornament